Democracy under Pressure Resilience or Retreat? - van Beek, Ursula (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"This book is essential reading. Against the backdrop of a 15-year democratic recession, the question of why some countries become more democratic while others see growing authoritarianism is one of the most pressing of our era. This inspired volume cleverly leverages a comparative approach to provide new insights into the sources of democratisation and backsliding, making an important and timely contribution." -Nic Cheeseman, Professor of Democracy, University of Birmingham, UK "This book is a delightful guide and a remarkable must-read for all those concerned with the decline of liberal democracies. This new book by a group of scholars dealing with the topic for quite a time is both a follow-up to their past tales about democracies across cultures and continents and a brand-new approach to its contemporary problems. The theoretical arguments are backed by convincingly constructed comparative country case-studies. It is accessible and fascinating. This book will be widely read by students, social scientists, policymakers, and-I hope-politicians." -Radoslaw Markowski, Professor of Political Science, Polish Academy of Sciences, Poland" This book identifies the main factors shaping the fortunes of democracy globally. Why do some democracies in the same region and presumably subject to similar global influences remain stable while others regress? This is the question guiding all the authors of this edited book. In the search for answers, they examine 16 democracies in paired and tripled comparisons in sub-Saharan Africa, North and Latin America, East Asia, Western and Central Europe, along with two polar cases. Insights from the perspectives of history, political science, economics and international relations are offered along with a sketch of possible future scenarios. Combining approaches anchored in the analytical tradition with empirical case studies and given the broad range of topics, this book is bound to be of interest not only to students and practitioners of democracy but also to the broader academic and general readership. Ursula van Beek is the founder Director of the former Transformation Research Unit (TRU) and its successor CREDO, the Centre for the Study of Democracy, at the Department of Political Science at Stellenbosch University, South Africa.
1. Quo Vadis Democracy? Editor's Introduction -- 2. From the End of History to the End of the World? Global Challenges to Democracy -- 3. Economic and Political Implications of Technological Advances -- 4. Back to the Future: The Rise of Nationalist Populism -- 5. Global and Regional Developments at the Macro- and Micro-Levels -- 6. South Africa and Kenya -- 7. United States - Canada -- 8. Argentina-Chile-Uruguay -- 9. South Korea-Taiwan - The Philippines -- 10. Germany-Italy -- 11. Poland-Estonia -- 12. Democratic Resilience in Sweden -- 13. Varieties of Turkish Democracy: A Progress in Reverse? -- 14. Cross-Area Finding: Patterns and Prospects -- 15. Empirical Assessments: The Return of History -- 16. Looking Ahead: Democracy and Modernity.
Keywords: Comparative government; World politics; International relations; Comparative Politics; Political History; International Relations